2017
DOI: 10.7812/tpp/16-140
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism after a Single Normal Proximal Lower Extremity Venous Ultrasound

Abstract: Context:The optimal lower extremity venous ultrasound (US) protocol to diagnose deep venous thrombosis of the popliteal and more proximal veins is unclear.Objective: To determine the three-month rate of symptomatic venous thromboembolism (VTE) and clinical outcomes of inpatients and ambulatory patients with normal findings on single venous ultrasound of the popliteal and more proximal veins (single proximal US).Design: Single proximal US results and clinical data of all inpatient and ambulatory patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Subgroup analyses were hampered by a lack of studies per group (S8 Appendix). Sensitivity analyses including all studies regardless of quality showed comparable results (n = 9 [10][11][12]19,33,38,43,44,47]; see S9 Appendix for summary estimates).…”
Section: Diagnostic Accuracy In Studies Using Clinical Follow-up As Rmentioning
confidence: 86%
“…Subgroup analyses were hampered by a lack of studies per group (S8 Appendix). Sensitivity analyses including all studies regardless of quality showed comparable results (n = 9 [10][11][12]19,33,38,43,44,47]; see S9 Appendix for summary estimates).…”
Section: Diagnostic Accuracy In Studies Using Clinical Follow-up As Rmentioning
confidence: 86%
“…A Whole-leg CUS is a single examination of the distal and proximal deep veins of the lower extremity in the same setting. [26][27][28]32,61 PTP by Wells' score, expertise, cost, feasibility were among the important factors to determine which CUS protocol was being used. 26 The clinical relevance and anticoagulant treatment strategies of IDDVT is a major factor in debating US strategies and IDDVT will determine the future of whole-leg CUS (The Guidelines and Algorithms).…”
Section: Imaging Techniques Used In Diagnosing Dvtmentioning
confidence: 99%
“…26 The clinical relevance and anticoagulant treatment strategies of IDDVT is a major factor in debating US strategies and IDDVT will determine the future of whole-leg CUS (The Guidelines and Algorithms). 26 The serial CUS could be dropped altogether and no need for a whole-leg CUS; 61 symptomatic VTE occurred in less than 1% in the study of Mitsunaga MM et al 61 after an initially normal single proximal CUS, and a whole-leg CUS has limitations in the diagnostic performance at the calf level and some of the positive findings might even be false positives. 61 But high risk groups; previous VTE and/or an active malignancy, and recent hospitalization/major surgery and/or immobilization, should be treated differently.…”
Section: Imaging Techniques Used In Diagnosing Dvtmentioning
confidence: 99%
“…In the USA, this condition has a prevalence of approximately 100:100,000 individuals every year, with the incidence increasing with age. Thus, it seems that in children under the age of 15 years, the incidence is of approximately 5:100,000 cases, whereas in adult above the age of 80 years, this condition can reach an incidence of 500:100,000 cases (4). Even though a precise estimation of VTE in children cannot be established because there are only a few reported prospective studies, these studies underlined an annual incidence of pediatric VTE between 0.07-0.14:10,000 children and 5.3:10,000 admissions to pediatric hospitals (5).…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for the diagnosis of DVT is angio-CT. Recently, venous compression ultrasound is the initial diagnostic tools used in these cases due to the advantages related to the costs, availability and safety profile (4,6). Current treatment of VTE includes unfractionated heparin, low molecular weight heparin, and warfarin, but fondaparinux and direct thrombin inhibitors can also be used (7).…”
Section: Introductionmentioning
confidence: 99%